A confirmatory factor analysis model of servant leader of school director under the office of the Vocational Education Commission in Thailand - Sisan, Boonchan (My University, 2017)
This research aims to develop and examine the Goodness-of-Fit Index of Confirmatory Factor Analysis (CFA) in servant leader of school director under the Office of the Vocational Education Commission (OVEC). The result is based on the empirical data. The sample group consisted of 247 school directors under the OVEC. The samples were taken using Multi - Stage Sampling randomized technique. Research instrument was questionnaire which had 0.80 - 1.00 for item objective congruence, discriminative power with 0.46 - .80, and reliability of .95. The data analysed by Confirmatory Factor Analysis (CFA). The study shows the servant leader of school director under the OVEC consists of six factors: Appreciating of Others, Developing Others, Developing Community, moral Expressions, Supporting Leadership, and Using Leadership Together. The results of examination of the Goodness-of-Fit Index of Confirmatory Factor Analysis (CFA) found the model fit indexes based on the empirical data were =280.89; df=252; P-value=0.10204; Relative =1.11; RMSEA=0.022; NFI=0.98; RMR=0.016; SRMR=0.041; GFI=0.92; AGFI=0.89; NIF=0.98; IFI=1.00; CFI=1.00; CN=252.56. The factor loadings of six factors were from 0.73 - 0.94 and factor loadings of indicators were from -0.39 - 0.57.
Keywords: And Using Leadership Together; Appreciating of others; Developing community; Developing others; Moral expressions; Servant leader; Supporting Leadership